2015
DOI: 10.1007/s11010-015-2506-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated miR-28-5p in human hepatocellular carcinoma correlated with tumor proliferation and migration by targeting insulin-like growth factor-1 (IGF-1)

Abstract: Hepatocellular carcinoma (HCC) is a rapidly progressing, incurable cancer that frequently spreads to portal vein and lung. New insights are needed to identify therapeutic targets to prevent or retard HCC metastatic progression. Because microRNAs (miRNA) often act as tumor regulators, we investigated their role in preclinical models of HCC. Here we found miR-28-5p is a liver-relevant anti-proliferative miRNA whose expression, functions, and mechanisms were analyzed in human hepatoma cells, HepG2 and Huh7. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 33 publications
2
40
2
Order By: Relevance
“…Through gene expression profiles and bioinformatics analysis, we identified IL‐34 as a direct target for miR‐28‐5p, and we further confirmed that the impact of miR‐28‐5p deficiency on regulation of HCC progression in vivo was dependent on this target. A recent report revealed that overexpression of miR‐28‐5p and an miR‐28‐5p mimic suppressed proliferation of HCC cells by targeting insulin‐like growth factor 1 . This observation, which contradicts our study results, may stem from the difference between cell lines and the vectors that were used to overexpress miR‐28‐5p.…”
Section: Discussioncontrasting
confidence: 99%
“…Through gene expression profiles and bioinformatics analysis, we identified IL‐34 as a direct target for miR‐28‐5p, and we further confirmed that the impact of miR‐28‐5p deficiency on regulation of HCC progression in vivo was dependent on this target. A recent report revealed that overexpression of miR‐28‐5p and an miR‐28‐5p mimic suppressed proliferation of HCC cells by targeting insulin‐like growth factor 1 . This observation, which contradicts our study results, may stem from the difference between cell lines and the vectors that were used to overexpress miR‐28‐5p.…”
Section: Discussioncontrasting
confidence: 99%
“…The results displayed by our present work support the conclusion that miR-28 may mediate oxidative stress-induced cellular injury. Previous investigations on cancers demonstrated that miR-28 serves to inhibit cancer development or progression (Almeida et al 2012;Shi and Teng 2015;Zhou et al 2016), and the pro-apoptotic effect of miR-28 on cardiomyocytes in the present study stands in accordance with these studies, further reinforcing the current understanding of the function of miR-28.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several microRNAs, such as miR-21, miR-874, and miR-484, which control the tumorigenicity are also found to exert critical effects in the cell death of cardiomyocytes (Wang et al , 2013Wei et al 2014). Recent studies have shown that miR-28 is involved in multiple cancers, and it has tumor-suppressive functions in B cell lymphomas and hepatocellular carcinoma (Schneider et al 2014;Shi and Teng 2015). The role of miR-28 in the heart has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, metastasis is the most fatal event during disease progression; it accounts for approximately 90% of patient deaths. 52 In this study, miR-28-5p expression was down-regulated in CRC samples compared with that in normal colon samples, and the down-regulation of miR-28-5p forecasted a poor prognosis for CRC patients, suggesting that this miRNA plays a tumour-suppressive role. 43 Metastasis formation is a major obstacle in CRC therapy.…”
Section: Discussionmentioning
confidence: 55%